2021
DOI: 10.1007/s00417-021-05113-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery after macula involving retinal detachment and its correlation with preoperative biomarkers in optical coherence tomography

Abstract: To introduce an ETDRS grid-based classification for macula involving retinal detachment (MIRD) with or without center (foveal) involvement and to identify biomarkers in preoperative optical coherence tomography (OCT) associated with a favorable postoperative functional outcome in eyes with center involving retinal detachment (CIRD). One hundred and two eyes of 102 consecutive patients (f/m: 35/67) with primary rhegmatogenous retinal detachment, preoperative evidence of MIRD (perifoveal involvement of ≤ 6.0 mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Our data could not detect prognostic effects of preoperative parameters such as foveal height of detachment, degrees of macular areas detached, shorter duration of macular detachment or visual loss until surgery, as is commonly established [ 1 , 5 , 6 , 22 , 23 ]. The subgroup without foveal detachment shows better baseline and final visual acuity, in accordance with these reports, but our subgroups were too small to make a statistical conclusion ( S2 Table ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our data could not detect prognostic effects of preoperative parameters such as foveal height of detachment, degrees of macular areas detached, shorter duration of macular detachment or visual loss until surgery, as is commonly established [ 1 , 5 , 6 , 22 , 23 ]. The subgroup without foveal detachment shows better baseline and final visual acuity, in accordance with these reports, but our subgroups were too small to make a statistical conclusion ( S2 Table ).…”
Section: Discussionmentioning
confidence: 59%
“…Preoperative features of optical coherence tomography (OCT) such as photoreceptor length, height of foveal detachment, inner retinal undulation and inner retinal separations have been discussed as biomarkers of visual recovery [ 3 , 4 ]. In cases of foveal detachment, visual recovery seems better if the macula is only partially detached, compared to a complete macular detachment [ 5 ]. Moreover, a preserved foveal depression despite foveal detachment seems predictive of a better functional outcome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klaas and colleagues used SD-OCT to define a more precise classification of rhegmatogenous retinal detachment according to the state of the macula and the fovea. They also showed that the grade of retinal detachment and the extent of the cystoid macular edema were good preoperative biomarkers to predict functional recovery in eyes with detached fovea [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the potential biomarkers predicting functional recovery, the grade of detachment and the extent of cystoid macular edema seems promising in eyes with a detached fovea, as well as the integrity of the ellipsoid zone [ 14 , 30 ]. The extent of the detachment, the postoperative foveal contour, the integrity of the ellipsoid zone and of the external limiting membrane, and the presence of outer retinal folds, seem to be predictors of visual prognoses and metamorphopsia following a successful vitrectomy [ 12 , 15 , 16 , 17 , 22 , 28 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that macular-on status had a predictive role in functional recovery after DEX-I for recalcitrant CME. RRD-related macular status has a strong correlation with visual recovery after retinal surgery [ 35 ]. In particular, macular OCT biomarkers, including the presence and extension of cystoid edema before surgery and outer retinal layer integrity after surgery, correlate with functional outcomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%